Effect of over tree cooling irrigation on ‘Bosc’ pear orchards microclimate - Lakatos, L.; Sun, Z.; Zhang, J.; Soltész, M.; Nyéki, J. (International Journal of Horticultural Science, 2016)
Irrigation in some countries is a horticultural practice mainly used only to supply water. At the same time the use of microsprinklers have a powerful infl uence on the changes of temperature in orchards. When the air’s temperature is high (about 20 °C or higher) the evaporative cooling irrigation signifi cantly decreases the plants’ surface temperature and air temperature. The cooling effect is stronger when the air is dryer. By using cooling irrigation regularly, canopy temperature can be decreased so that the beginning of blooming can be delayed. Also if the blooming is early and frost probability is high, serious damages can happen in orchards. The benefi cial effect of cooling irrigation is the temperature reduction and frost protection. In March 2010, one month earlier than the expected blooming an irrigation system was established to produce anti-frost treatment and regulate the micro-climate of a Bosc pear orchard which belongs to the University of Debrecen (Hungary). The objective of sprinklers was to cool the air by increasing water evaporation and relative humidity. The position of the micro-sprinklers was planned in three levels (around the tree trunks, a few cm near to the soil surface, in the crown region and above the crown, a half meter higher). The results showed that the water sprayed in the orchard by micro-jets infl uenced decisively the temperature of the plantation. At higher temperatures (around 20 °C), the drop of temperature may attain 5–7 °C. A low relative humidity of the air may increase the relative effect. When water was applied at intervals of 15 minutes for ten times a day from 8 am to 18 pm, the air, fl owers and bud’s surface temperature could be kept low. At certain days when the temperature was higher than 10 °C, irrigation was used at night time in similar 15 minutes intervals, from 18 pm and 6 am. The beginning of bloom could be delayed for more than ten days. The Bosc pear variety blooming dynamics was characterized by a logistic curve in the treated as well as in the control plot. In the treated plot, the curve was steeper than in the control one in spite of the equal temperatures measured in the plots. Under Hungarian climatic conditions, the method was successfully used to delay blooming dates. The main result was the diminution of the frost damage in the spring that assured pears yields.